Filem sebagai cerminan identiti budaya: Analisis terhadap karya Deddy Mizwar / Vina Effendi - Vina, Effendi (2016)
This research is a textual analysis study to reveal the cultural identity and political thought of the films by Deddy Mizwar through a cultural studies and textual framework of critical discourse approach. The films growth in the Soeharto era that restrained the freedom of expression and communication through media resulted in the depravity of the film quality because it was oriented in comedy, horror and porn. Films are just an entertainment for elites who hate to be criticized and laborers who are blind knowledge. The films of Nagabonar Jadi 2 and Alangkah Lucunya Negeri Ini are selected as study materials for the dare content criticizing the corrupt parties (the monarchy and parliamentarians) and the appealing to the goodness such as pursuing knowledge, showing tolerance, loving, respecting women and appreciating the history of the nation. The films that threaten the hegemony are managed to get various awards. The cultural studies concerning about cultural identity and textual framework of critical discourse analysis meets the holistic approach in this research. Fairclough’s three-dimensional theory is used to evaluate the local film industry from the perspective of Macro, Meso and Micro. The macro analysis finds that there are internal and external conflicts among the Board of National Film that make him difficult to play the role effectively. The chronology of history shows this organization was once suspended and inactive. Meso analysis finds that the number of film titles released by Demi Gisela Citra Sinema is less than Rapi Films, Sinemart and MD Entertainment. Although the competition between film production companies is very strong, but the film quality determines the popularity of the company in front of the general public. In accordance with the thought of the company owner, Deddy Mizwar, the film produced must meet the good quality and appeal to the goodness. Thus after the reformation era, the era of freedom to express was protected by the vii Law Act No 9 of 1998, the company are then dare to begin producing films to sue the corrupt monarchy and parliamentarians. This research is also enhanced by micro analysis was finds similar message from both of the films in the textual studies about education, affection, the habits of Indonesian people, politics and religion. Finally, this research found that films is lens of cultural identity.